1996
DOI: 10.1007/bf02088227
|View full text |Cite
|
Sign up to set email alerts
|

Short-term treatment of gastric ulcer

Abstract: Gastric ulcer is relatively infrequent, and clinical trails are often based on small-sized samples. The aim of this study was to define the "gold standard" therapy of active gastric ulcer. We included all single- or double-blind clinical trials on the short-term treatment of gastric ulcer. All the articles published over the period 1977-1994 were reviewed. Meta-analysis was done with both fixed and random effect models; results were shown using Galbraith's radial plot. Forty-eight papers comprising 52 studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Comparison analysis demonstrates the usefulness of PPIs and H 2 RAs in healing artificial ulcers after ESD, while meta-analysis shows significantly higher ulcer healing rates with PPIs than with H 2 RAs [82, 83]. For example, Ye et al [84] reported that active ulcers remained at a higher incidence after four weeks of H 2 RA treatment than of PPI treatment in artificial ulcers.…”
Section: Anti-acid Drugs For Artificial Ulcersmentioning
confidence: 99%
“…Comparison analysis demonstrates the usefulness of PPIs and H 2 RAs in healing artificial ulcers after ESD, while meta-analysis shows significantly higher ulcer healing rates with PPIs than with H 2 RAs [82, 83]. For example, Ye et al [84] reported that active ulcers remained at a higher incidence after four weeks of H 2 RA treatment than of PPI treatment in artificial ulcers.…”
Section: Anti-acid Drugs For Artificial Ulcersmentioning
confidence: 99%